Implementasi dan Pengembangan Quick Response Code pada Sistem Digitalisasi Laboratorium di Laboratorium Jurusan Teknik Elektromedik Politeknik Kesehatan Jakarta II - Gita Rindang Lestari; Mamurotun Mamurotun; Nur Hasanah Ahniar (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
The laboratory is one of the vital facilities in vocational education. Based on observations in the Laboratory of the Department of Electromedical Engineering at Poltekkes Kemenkes Jakarta II, the equipment operation instructions/SOP documents are still using HVS paper, which is manually attached to walls or hung on the equipment itself. This method causes the instruction documents to deteriorate quickly and be easily lost, thereby disrupting laboratory operations. With the rapid advancement of technology, this issue can be addressed through the digitalization of laboratory documents. The goal of this digitalization is to enhance document storage security, simplify access, and make the instruction documents more efficient in terms of size. One practical solution proposed is the implementation of a Quick Response Code (QR Code) system. QR Codes not only improve document storage security and information access speed but also maintain functionality even when the code is physically damaged by up to 30%. This research was conducted in the Laboratory of the Department of Electromedical Engineering over seven months, from June 2024 to December 2024. The research methodology involved seven stages: collecting instruction documents, system design, system development, QR Code testing using a QR scanner, data collection, data processing, and result analysis. In testing the functionality of the QR Code, a blackbox testing method was used to ensure that the generated QR Codes accurately displayed the equipment operation instructions. The identification results showed that 174 pieces of equipment in the Electromedical Engineering Laboratory have been equipped with QR Codes. The research findings indicate that the implementation of QR Codes successfully enhanced the security of instruction document storage and facilitated easier access for laboratory users. Thus, the digitalization of instruction documents through QR Codes is expected to improve the efficiency of laboratory management, reduce the risk of document damage and loss, and support a more modern and integrated laboratory operation.